PERENCANAAN KAWASAN TRANSIT ORIENTED DEVELOPMENT (TOD) MENUJU SISTEM TRANSPORTASI BERKELANJUTAN DI STASIUN MONOREL BEKASI TIMUR - , VERA APRILIA V ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The number of the commuters from Bodetabek to Jakarta was 3,6 million people per day, in 2011. The biggest number of those commuters came from Bekasi which are 1.3 million people per day. From that number, there was 77% of commuters went to Jakarta using private vehicles and causing traffic jam. The government has been planning the procurement of mass transportation with the construction of monorail station in East Bekasi. The construction site of monorail station can be developed as a Transit Oriented Development (TOD) Area which is an area with mixed land use. TOD area is expected to be one of the attractions for commuters to use mass transportation for their needs. This matter will impact a decrease of utility of private transportation and reduction of traffic jam. TOD planning in East Bekasi are based on TOD theory which is formulated by Calthorpe (1993) and urban design theory which is formulated by Shirvani (1985). Proccess of planning includes analyzing Kota Bekasi as macro data, site plan and monorail as micro data, sustainable transportation as the theory, commuter trip, and best practice of TOD in Hong Kong. And then, based on the results of that analysis, the potentials and regional planning issues can be obtained. The main potential is a project for monorail station and the main problems are urban sprawl and traffic jam. Elaboration of the potentials and problems will produce âDevelopment of Area Transit With The Transit Oriented Development Concept to Implement Sustainable Transportation System in 2019\" planning. This plan emphasizes the provision of mixed use that is integrated with the transportation system (monorail station) and the provision of pedestrian friendly area (pedestrian ways). It will create a city which is livable and walkable. This plan will be the most effective solution for integrated land use and sustainable transportation in Bekasi and Jakarta.